Infections and schizophrenia - V. A. Orlova; I. I. Mikhailova; V. A. Zinserling (Журнал инфектологии)
This paper provides a critical review of the literature, demonstrating a certain pathogenetic role of various infections, primarily viruses from the herpes and chlamydia groups, in the development and progression of schizophrenia, including published results of the authors’ own long-term studies.